The Role of Motivation and Professional Competence in Improving Teacher Performance - Muhammad Fachmi; Mustafa Mustafa; Ali Murdhani Ngandoh (MO.RI Publishing, 2021)
Abstract: This study aims to analyze the role of work motivation and professional competence in improving the performance of Vocational High School teachers in Soppeng Regency, as well as which variables are most dominant in influencing the improvement of teacher performance. Researchers took a sample of 72 teachers from five vocational schools in Soppeng Regency with the sampling technique, namely random sampling. The data analysis technique used is multiple linear regression analysis with SPSS software. The results showed that work motivation has a positive and significant effect on teacher performance, meaning that if the work motivation is higher, the teacher's performance will also increase. In addition, professional competence also has a positive and significant effect on teacher performance, so that if professional competence is getting better, teacher performance will also increase. Researchers also found that work motivation is the most dominant variable affecting the improvement of teacher performance in schools. Keywords: Work Motivation, Professional Competence, Teacher Performance Abstrak: Penelitian ini bertujuan untuk menganalisis peranan motivasi kerja dan kompetensi profesional dalam meningkatkan kinerja guru Sekolah Menengah Kejuruan di Kabupaten Soppeng, serta variabel manakah yang paling dominan dalam mempengaruhi peningkatan kinerja guru. Peneliti mengambil sampel sebanyak 72 orang guru yang berasal dari lima SMK di Kabupaten Soppeng dengan teknik penentuan sampel yaitu dengan random sampling. Teknik analisis data yang digunakan yaitu analisis regresi linier berganda dengan software SPSS. Hasil penelitian menunjukkan bahwa motivasi kerja berpengaruh positif dan signifikan terhadap kinerja guru, artinya jika motivasi kerja semakin tinggi maka kinerja guru juga akan semakin meningkat. Disamping itu, kompetensi profesional juga berpengaruh positif dan signifikan terhadap kinerja guru, sehingga apabila kompetensi profesional semakin baik maka kinerja guru juga akan mengalami peningkatan. Peneliti juga menemukan bahwa motivasi kerja merupakan variabel yang paling dominan mempengaruhi peningkatan kinerja guru di sekolah. Kata Kunci: Motivasi Kerja, Kompetensi Profesional, Kinerja Guru